The Influence of Supply Chain Integration on Supply Chain Performance of Auto-Parts Manufacturers in Thailand: A Mediation Approach - Wissawa Aunyawong; Preecha Wararatchai; Chattrarat Hotrwaisaya (International Journal of Supply Chain Management, 2020)
By reason of supply chain management difficulties of many firms from various industries in Thailand, it is crucial to comprehend which determining factor may tackle these difficulties. This research aims to study the effect of supply chain integration (SCI) on supply chain performance (SCP) by reflecting the mediation effects of supply chain collaboration (SCC) and logistics flexibility (LGF). The research design was based on the quantitative explanatory study. Using a confirmatory factor analysis, the study examined interactive dimensions of SCP, SCC, LGF, and SCI. The research model consisted of 4 latent variables assessing 13 observed variables. The only exogenous latent variable was SCI, whereas endogenous latent variables were SCC, LGF, and SCP. The stratified random sampling was used to select the questionnaire respondents. Data from a total 321 complete surveys were acquired from top managers working for auto-parts manufacturing companies in Thailand. The hypotheses were tested by using structural equation modeling (SEM). The results supported that SCI enabled auto-parts manufacturing firms to improve SCP successfully, and that SCC and LGF played an important role in mediating the effect of SCI on SCP. This research recommended that companies should consider strategies enhancing SCI, SCC, and LGF as they can increase their SCP.